By any other name eaudiobook A novel. - Picoult, Jodi (Books on Tape, 2024)
From the New York Times bestselling co-author of Mad Honey comes an “inspiring” ( Elle ) novel about two women, centuries apart—one of whom is the real author of Shakespeare’s plays—who are both forced to hide behind another name. “You’ll fall in love with Emilia Bassano, the unforgettable heroine based on a real woman that Picoult brings vividly to life in her brilliantly researched new novel.”—Kristin Hannah, author of The Women Young playwright Melina Green has just written a new work inspired by the life of her Elizabethan ancestor Emilia Bassano. But seeing it performed is unlikely, in a theater world where the playing field isn’t level for women. As Melina wonders if she dares risk failure again, her best friend takes the decision out of her hands and submits the play to a festival under a male pseudonym. In 1581, young Emilia Bassano is a ward of English aristocrats. Her lessons on languages, history, and writing have endowed her with a sharp wit and a gift for storytelling, but like most women of her day, she is allowed no voice of her own. Forced to become a mistress to the Lord Chamberlain, who oversees all theatre productions in England, Emilia sees firsthand how the words of playwrights can move an audience. She begins to form a plan to secretly bring a play of her own to the stage—by paying an actor named William Shakespeare to front her work. Told in intertwining timelines, By Any Other Name, a sweeping tale of ambition, courage, and desire centers two women who are determined to create something beautiful despite the prejudices they face. Should a writer do whatever it takes to see her story live on . . . no matter the cost? This remarkable novel, rooted in primary historical sources, ensures the name Emilia Bassano will no longer be forgotten. This audiobook contains a bonus PDF with Shakespearean references, Sources and Resources, and an image from the book.